2022
DOI: 10.3390/ijms232012075
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Enhances Drought Tolerance in Rice Seedlings by Modulating Antioxidant Systems, Osmoregulation, and Corresponding Gene Expression

Abstract: Rice is the third largest food crop in the world, especially in Asia. Its production in various regions is affected to different degrees by drought stress. Melatonin (MT), a novel growth regulator, plays an essential role in enhancing stress resistance in crops. Nevertheless, the underlying mechanism by which melatonin helps mitigate drought damage in rice remains unclear. Therefore, in the present study, rice seedlings pretreated with melatonin (200 μM) were stressed with drought (water potential of −0.5 MPa)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 51 publications
4
12
1
Order By: Relevance
“…To alleviate this deleterious effects, plants produce a lots of ROS-scavenging enzymes, such as SOD and POD, which could ensure their survival under drought stress 17. In a previous study, Rayyan Khan et al found that drought-resistant tobacco mitigated the oxidative damage by increasing the antioxidant enzyme activities and elevated the content of antioxidant substances 18 . The same conclusion was obtained by Chengke Luo et al in a drought stress study in rice, rice sprayed with melatonin (drought regulator) could accumulate more SOD and POD to mitigate the damage caused by drought stress to seedlings 19 . Osmoregulation is another important defense strategy under drought stress, which effectively reduce the water potential of plant cells, prevent cell dehydration and ensure normal plant growth 20 .…”
Section: Discussionsupporting
confidence: 77%
“…To alleviate this deleterious effects, plants produce a lots of ROS-scavenging enzymes, such as SOD and POD, which could ensure their survival under drought stress 17. In a previous study, Rayyan Khan et al found that drought-resistant tobacco mitigated the oxidative damage by increasing the antioxidant enzyme activities and elevated the content of antioxidant substances 18 . The same conclusion was obtained by Chengke Luo et al in a drought stress study in rice, rice sprayed with melatonin (drought regulator) could accumulate more SOD and POD to mitigate the damage caused by drought stress to seedlings 19 . Osmoregulation is another important defense strategy under drought stress, which effectively reduce the water potential of plant cells, prevent cell dehydration and ensure normal plant growth 20 .…”
Section: Discussionsupporting
confidence: 77%
“…A noticeable reduction was observed in IR50 plants when treated with NPs ( Khan et al., 2022 ). The possible phenomena may be the initiation of melatonin synthesis in C. sativum that improved the activity of antioxidant enzymes ( Luo et al., 2022 ). This may ameliorate the drought tolerance through a reduction in ABA and increasing the osmo-protectants (proline and chlorophyll content) as described by Luying Sun et al.…”
Section: Discussionmentioning
confidence: 99%
“…Of them, soil drought is one of the most severe environmental stressors leading to a decrease in plant productivity. This decrease slows down plant growth or accelerates plant aging by affecting various plant physiological and biochemical processes (Luo et al 2022;Talbi et al 2020). Drought can cause plant chloroplast degradation, resulting in damage to the photosynthetic system, inhibition of photosynthetic electron transfer, an increase in excess excitation energy, and ultimately accumulation of reactive oxygen species (ROS) in the chloroplast.…”
Section: Introductionmentioning
confidence: 99%